Associations of maternal arsenic exposure with adult fasting glucose and insulin resistance in the Strong Heart Study and Strong Heart Family Study. (April 2020) - Tinkelman, Naomi E.; Spratlen, Miranda Jones; Domingo-Relloso, Arce; Tellez-Plaza, Maria; Grau-Perez, Maria; Francesconi, Kevin A.; Goessler, Walter; Howard, Barbara V.; MacCluer, Jean; North, Kari E.; Umans, Jason G.; Factor-Litvak, Pam; et al.
Highlights: Maternal arsenic exposure may play a role in risk for adult-onset type 2 diabetes. Maternal arsenic exposure has a greater effect on diabetes than adult arsenic. Adult offspring BMI may mediate the association. Long-term epigenetic effects of maternal arsenic exposure are likely involved. Abstract: Experimental and prospective epidemiologic evidence suggest that arsenic exposure has diabetogenic effects. However, little is known about how family exposure to arsenic may affect risk for type 2 diabetes (T2D)-related outcomes in adulthood. We evaluated the association of both maternal and offspring arsenic exposure with fasting glucose and incident T2D in 466 participants of the Strong Heart Family Study. Total arsenic (ΣAs) exposure was calculated as the sum of inorganic arsenic (iAs) and methylated (MMA, DMA) arsenic species in maternal and offspring baseline urine. Median maternal ΣAs at baseline (1989–91) was 7.6 µg/g creatinine, while median offspring ΣAs at baseline (2001–03) was 4.5 µg/g creatinine. Median offspring glucose in 2006–2009 was 94 mg/dL, and 79 participants developed T2D. The fully adjusted mean difference (95% CI) for offspring glucose was 4.40 (−3.46, 12.26) mg/dL per IQR increase in maternal ΣAs vs. 2.72 (−4.91 to 10.34) mg/dL per IQR increase in offspring ΣAs. The fully adjusted odds ratio (95%CI) of incident T2D was 1.35 (1.07, 1.69) for an IQR increase in maternal ΣAs and 1.15 (0.92, 1.43) for offspring ΣAs. The association of maternal ΣAs with T2D outcomes were attenuated with adjustment for offspring adiposity markers. Familial exposure to arsenic, as measured in mothers 15–20 years before offspring follow-up, is associated with increased odds of offspring T2D. More research is needed to confirm findings and better understand the importance of family exposure to arsenic in adult-onset diabetes.